Parameter (Voltage, Current, Time) study for thermoelectric cooler (TEC) for automobile air-conditioner - Amir Izzani, Mohamed; Siti Nor Aisyah, Burhanudin; M. S., Jadin (Springer Singapore, 2018)
This research is designed to build a controller to control the cold side temperature of thermoelectric material called Thermoelectric Coolers (TECs). This work deals with a useful control scheme to impose a user defined cold tem-perature on an airconditioning used as cold sources for Thermoelectric Coolings characterization. These devices used in both power supply and cooler configura-tions. During the experiments, the thermoelectric material was driven two ways, by manually supply voltage using a power supply and then by a PWM signal generated by an Arduino-UNO board on which the ON-OFF controller is imple-mented. This work includes major results of tests that were conducted in order to identify the relationship between voltage and current flow in the TECs module to temperature gradient of two surfaces and the time required to cool ambient air & impact of different cooling methods to remove heat from TECs surfaces.